2011
DOI: 10.1088/0953-8984/23/11/112205
|View full text |Cite
|
Sign up to set email alerts
|

The giant anomalous Hall effect in the ferromagnet Fe3Sn2—a frustrated kagome metal

Abstract: The kagome-bilayer material Fe(3)Sn(2) has recently been shown to be an example of a rare class of magnet-a frustrated ferromagnetic metal. While the magnetism of Fe(3)Sn(2) appears to be relatively simple at high temperature, with localized moments parallel to the c-axis (T(C) = 640 K), upon cooling the competing exchange interactions and spin frustration become apparent as they cause the moments to become non-collinear and to rotate towards the kagome plane, forming firstly a canted ferromagnetic structure a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 45 publications
5
93
1
Order By: Relevance
“…The Fe atoms form bilayers of offset kagome networks, with Sn atoms throughout the kagome layers as well as between the kagome bilayers. [33,34] In this communication, we report that magnetic skyrmionic bubbles with various spin textures can indeed be realized in the single crystals of Fe 3 Sn 2 at room temperature. [29][30][31][32] Recently, a large anomalous Hall effect was observed in this material, which is strongly related to the frustrated kagome bilayer of Fe atoms.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 74%
See 1 more Smart Citation
“…The Fe atoms form bilayers of offset kagome networks, with Sn atoms throughout the kagome layers as well as between the kagome bilayers. [33,34] In this communication, we report that magnetic skyrmionic bubbles with various spin textures can indeed be realized in the single crystals of Fe 3 Sn 2 at room temperature. [29][30][31][32] Recently, a large anomalous Hall effect was observed in this material, which is strongly related to the frustrated kagome bilayer of Fe atoms.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 74%
“…[24] The sharp contrast between the dark stripe domains and the bright walls suggests that the domains possess out-of-plane magnetizations and are separated by Bloch domain walls. [32][33][34] This feature suggests that the spin texture of domains in the bulk and LTEM samples show little differences. Interestingly, we found that when the temperature was lower than 130 K, the stripe domains disappeared and vortex domains formed, indicating that the spin starts to lie into the ab-plane below 130 K. The critical temperature of the LTEM sample coincides with that of the bulk sample, but with a slight deviation.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 94%
“…Here, the anomalous Hall effect has been attributed to the combined effect of non-collinear antiferromagnetic spin texture and electronic band structure 12,13 . A large anomalous Hall coefficient, reported for Fe 3 Sn 2 15,16 cannot be described by the ferromagnetic component alone and is believed to be due to the massive quasi-2D Dirac cones near the Fermi energy. Likewise, the large AHE observed in frustrated systems such as Pr 2 Ir 2 O 7 has been attributed to the non-coplanar spin texture 27 .…”
Section: Resultsmentioning
confidence: 96%
“…Reformulation of the SOC-induced intrinsic mechanism of AHE in ferromagnets to the Berry phase curvature in momentum space has been fruitful in predicting and describing the AHE in several other systems, including Weyl (semi)metals 3 , non-collinear antiferromagnets 4 , non-coplanar magnets 57 , and other nontrivial spin textures 811 . Recent observations of the large anomalous Hall effect in metals with possible Weyl 1214 and massive Dirac fermions 15,16 and/or complex spin textures, e.g., skyrmion bubbles 17 , have generated interest in such materials, especially for the role of correlated topological states in the emergent electronic properties. Here we present a large AHE in CoNb 3 S 6 that cannot be understood in terms of conventional mechanisms of the AHE.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by Kagome-like bilayers of Fe separated by a layer of Sn. A second type of Sn atom occupies the hexagonal vacancies in each of the Kagome layers [11,12]. Each Fe atom is surrounded by 11 Fe atoms and 11 Sn atoms.…”
mentioning
confidence: 99%